Association of Calpastatin (CAST) Gene with Growth Traits and Carcass Characteristics in Bali Cattle - R. Putri; R. Priyanto; A. Gunawan; . Jakaria (Faculty of Animal Science, Bogor Agricultural University, 2015)
Calpastatin (CAST) gene is well known as an inhibitor of muscle protein degradation and relates to muscle growth and meat tenderness. The objective of this study was to determine the association of CAST gene with growth traits and carcass characteristics in Bali cattle. A number of data from 35 Bali bulls were collected from BPTU Bali Cattle to obtain growth traits, carcass characteristics, and blood samples. Polymorphism of CAST gene in Bali bulls was analyzed by using PCR-RFLP and DNA sequencing. The association of CAST gene with growth traits and carcass characteristics were analyzed by using General Linear Model (GLM). The result showed that there were two genotypes (GG and AG) of CAST gene with allele frequencies of 0.857 and 0.143, respectively, for G and A. Notably, mutation A to G occurred in 253 bp CAST fragment gene in Bali Cattle. Genotypes GG and AG of CAST gene significantly affected (P<0.05) the back-fat thickness and longissimus dorsi without a significant effect on the growth traits. It could be concluded that CAST gene had a potency as a marker gene for carcass quality in Bali cattle. Key words: Bali cattle, CAST gene, PCR-RFLP, polymorphism